(untitled) (Homoeopathy for All, 2022)
education provides a first-hand learning experience for students. It helps them to understand the functioning of the industry practice to correlate what they learn theoretically. Students get an opportunity to witness insights into the real working environment. It facilitates interaction with the manufacturing experts and helps to enhance the skills. It bridges the gap between theoretical knowledge and practical learning on the site/ field.In India, it is mandatory for homoeopathic graduates and post graduates (MD homoeopathic pharmacy) to visit the pharmaceutical industry to learn, observe and understand the process and preparation of homoeopathic medicines. This article gives an overview of the conduction of the industrial visits and their importance in pharmacy education.